Electrical Resistivity Tomography Investigations of Discontinuous Mountain Permafrost and its Relation to Elevation and Vegetation, Yukon - Kuntz, Zoé (Université d'Ottawa / University of Ottawa, 2016)
This study seeks to better understand the relationship between permafrost, elevation and vegetation cover, and to test the hypothesis that changes in mountain permafrost distribution and characteristics occur at vegetation type boundaries, as they do in latitudinal permafrost. Twelve electrical resistivity tomography (ERT) surveys were completed at vegetation transitions on selected slopes near Whitehorse and Dawson, Yukon, in July 2015. Wenner arrays with 2 m spacing between electrodes were used to complete the 80-280 m long surveys. Organic layer thickness and vegetative species composition were recorded in a transect for each survey. Ground-truthing via frost probing, pit digging, and ground temperature data from past and present weather stations aided in the analysis of ERT profiles. Several different resistivity patterns are present along the profiles. These patterns indicate some presence of permafrost along most of the slopes sampled. Exceptions include south-facing slopes free of permafrost and a few slopes with inconclusive resistivity interpretations due to complex resistivity patterns and ground-truthing difficulties. Overall, the results indicate that changes in permafrost distribution and characteristics do not consistently occur at vegetation type boundaries. At the scale examined, treeline is not as important a demarcation point for changes in permafrost as initially thought. Changes in organic mat, surficial geology, and snow cover (via micro-topography) appear to be as important as vegetation variation. These local controls play a significant role on permafrost distribution across both altitudinal and latitudinal forest-tundra ecotones. However, the propensity of alpine environments for cold air drainage and surface lapse rate inversions can create differences between the permafrost trends across altitudinal and latitudinal ecotones.
Keywords: ERT; Permafrost; Yukon